Policy vs. practice in sport and climate change: the perspectives of key actors in global sport and international development - Ali, Adam Ehsan; Millington, Rob; Darnell, Simon; Smith, Tavis (Frontiers in Sports and Active Living, 2024)
These calls for change have implications for every aspect of human activity, including sport, and, notably for this paper, have implications for the efforts within the global Sport for Development and Peace (SDP) sector. In recent years, SDP has grown in both size and scale, now comprised of a diverse body of organizations, including private, public and nongovernmental, that all leverage the "power of sport" in various ways to respond to a range of development challenges including (but not limited to) HIV/AIDS education, gender equity, and economic development (see Collison et al, 2019). Most recently, SDP has been directly connected to sustainable development, a concept which, among other issues, prioritizes environmental awareness, protection and remediation strategies that can help stem the tide of climate change. A recent policy brief from the UN Department of Economic and Social Affairs (UNDESA), for example, made clear these connections, noting that sport can play a key role in raising awareness of, and influencing behaviors towards climate action, making it a "low-cost" and "high-impact solution" to the climate crisis (UNDESA, 2022, p. 1). The report outlined four ways in which sport can be mobilized in the fight against climate change: as a "broad social platform" for influencing attitudes about climate change, with a range that "extends to almost all geographic areas and social backgrounds"; by playing "an important role in educating and raising awareness towards global warming and…environmental issues, including promoting a healthy, sustainable lifestyle"; as a tool "to reach sustainable development, including addressing global warming"; and through "the incorporation of sustainability standards in the sport industry (that) can have a ripple effect, contributing to sustainable production and consumption standards in other industries" (UNDESA, 2022, p.Overall, however, despite recognition of the scope of the climate crisis, and policies in place connecting sport to sustainable development, there remain concerns that the environment and climate change are rarely acknowledged within SDP activity and that even